Pulmonary pathology in vasculitis - Ambrogi, Elisa; Cavazza, Alberto; Smith, Maxwell L; Graziano, Paolo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Pulmonary involvement is frequent in vasculitis, particularly in ANCA-associated small vessel vasculitis. Laboratory and radiological data alone are often sufficient to confirm the clinical hypothesis, but sometimes the pathologist plays a crucial role in the differential diagnosis and the patient’s management. In this review, the pathologic features of pulmonary vasculitis and the pathologist’s role in this field are illustrated.